2009
DOI: 10.1021/ct900277m
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Carbon−Hydrogen and Hydrogen−Hydrogen Bonds by Copper−Nitrenes: A Comparison of Density Functional Theory with Single- and Multireference Correlation Consistent Composite Approaches

Abstract: Abstract:The kinetics and thermodynamics of copper-mediated nitrene insertion into C-H and H-H bonds (the former of methane) have been studied using several levels of theory: B3LYP/6-311++G(d,p), B97-1/cc-pVTZ, PBE1KCIS/cc-pVTZ, and ccCA (correlation consistent Composite Approach). The results show no significant difference among the DFT methods. All three DFT methods predict the ground state of the copper-nitrene model complex, L′Cu(NH), to be a triplet, while single reference ccCA predicts the singlet to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
2
20
1
Order By: Relevance
“…The overestimation of the metal nitrogen distances in the calculated structure by 0.05 – 0.08 Å are typical of DFT functionals. The optimized structure of 3–Sc (Scheme 1, Table S4) in the experimentally observed singlet state reveals a bent copper–nitrene unit with a k 2 –N,O binding mode of the NSO 2 R tosylnitrene ligand consistent with the results of a previous calculation 6a. The Cu–N(Sc)Ts distance in 3–Sc is calculated to be 0.045 Å shorter than the Cu–NHTs distance in 2 (Table S2).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…The overestimation of the metal nitrogen distances in the calculated structure by 0.05 – 0.08 Å are typical of DFT functionals. The optimized structure of 3–Sc (Scheme 1, Table S4) in the experimentally observed singlet state reveals a bent copper–nitrene unit with a k 2 –N,O binding mode of the NSO 2 R tosylnitrene ligand consistent with the results of a previous calculation 6a. The Cu–N(Sc)Ts distance in 3–Sc is calculated to be 0.045 Å shorter than the Cu–NHTs distance in 2 (Table S2).…”
supporting
confidence: 81%
“…The singlet (with a bent nitrene coordination mode) and the triplet (with linear nitrene coordination) states were theoretically calculated to be very close in energy, and the predicted ground state were found to depend strongly on the computational method used. 6 We report herein the Lewis–acid trapping of an elusive copper–tosyl nitrene (Cu II –N • Ts) species 3–Sc in presence of Sc(OTf) 3 in near–quantitative yields, and its detailed characterization by spectroscopy and theory, which leads to an unambiguous assignment of its electronic structure. Moreover, complex 3–Sc comprising the Cu II –N • Ts core rapidly abstracts hydrogen atoms from the strong C–H bonds of cyclohexane, thus providing a key precedent for the possible involvement of Cu II –N • Ts in oxidation catalysis.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We were eager to examine the related copper(II) amide [(Cl 2 NN)Cu-NHAd] as a potential intermediate formed by H-atom abstraction (HAA) of a C À H bond by a terminal copper-nitrene intermediate [(Cl 2 NN)Cu=NR]. [16,17] For instance, the b-diketiminato nickel nitrene [(Me 3 NN)Ni=NAd] reacts with 1,4-cyclohexadiene by HAA to give [(Me 3 NN)Ni-NHAd]. [18] Herein we describe synthetic studies that target a copper(II) amide intermediate in C À H amination [19,20] which reveal a bifunctional role for [(Cl 2 NN)Cu-NHAd] in stoichiometric CÀH functionalization and result in a new system for catalytic intermolecular CÀH amination with simple, unactivated alkylamines.…”
mentioning
confidence: 99%
“…Very recently, our group reported the spectroscopic characterization of a Lewis acid adduct of a cationic copper-tosylnitrene [Cu II -(N Ts • )Sc(OTf) 3 ] species ( 1 ; Ts = tosyl; Scheme 1), the electronic structure of which could be best described in terms of a Cu(II) ion antiferromagnetically coupled to a nitrene radical thereby stabilizing an open-shell singlet ground state 11 . Reactivity studies revealed that this species aminates sp 3 C–H bonds in substrates such as toluene and even cyclohexane in modest yields (21–35%). In this communication we now report the Lewis acid stabilization of a related copper nitrene species [Cu II -(N Mes • )Sc(OTf) 3 ] ( 2 ; Mes =mesityl; Scheme 1), where the electron withdrawing heteroatom Ts nitrene substituent of 1 is replaced by the electron donating Mes group in 2 .…”
mentioning
confidence: 99%